2002
DOI: 10.1006/jfbi.2002.2131
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity in brook charr: changes in caudal fin induced by water flow

Abstract: In the field, juvenile brook charr Salvelinus fontinalis inhabiting high-velocity water were found to have larger caudal fins and more slender bodies than those inhabiting low-velocity water. Young-of-the-year S. fontinalis were reared in either a high-or low-velocity treatment for 16 weeks and their morphology was measured bi-weekly. From the second to fourth weeks of the experiment onwards, fish reared in the high-velocity treatment had larger maximum caudal fin heights and deeper caudal peduncles than fish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
1
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(118 citation statements)
references
References 10 publications
6
108
1
3
Order By: Relevance
“…The only study that parallels ours in terms of phenotypic plasticity (Imre et al 2002) found that only caudal fin height and caudal peduncle depth showed a significant change with water velocity in brook charr. Here we found that water velocity induced changes in most of the traits measured, including those two traits.…”
Section: Phenotypic Plasticitysupporting
confidence: 58%
See 1 more Smart Citation
“…The only study that parallels ours in terms of phenotypic plasticity (Imre et al 2002) found that only caudal fin height and caudal peduncle depth showed a significant change with water velocity in brook charr. Here we found that water velocity induced changes in most of the traits measured, including those two traits.…”
Section: Phenotypic Plasticitysupporting
confidence: 58%
“…These differences may be related to two possible aspects. First, we have applied four water velocity treatments, whereas Imre et al (2002) applied only two. In many pairwise differences between two treatments, a number of traits would have not demonstrated significant effects.…”
Section: Phenotypic Plasticitymentioning
confidence: 99%
“…Many field and experimental studies have demonstrated that development in swift water can induce more streamlined bodies and narrower caudal peduncles in fishes (Claytor et al, 1991;McLaughlin and Grant, 1994;Imre et al, 2002). Streamlining theoretically improves performance and reduces drag during the sustained swimming required of individuals living in fast water (Webb, 1984;Bisson et al, 1988).…”
Section: Discussionmentioning
confidence: 97%
“…Among the many environmental factors that can induce intraspecific variation in fishes, the effects of differences in temperature (Hubbs, 1922;Barlow, 1961;Beacham, 1990), water velocity (Claytor et al, 1991;McLaughlin and Grant, 1994;Imre et al, 2002), and microhabitat (Lundberg and Stager, 1985;Layzer and Clady, 1987;O'Reilly and Horn, 2004) are among the best documented. Despite extensive research on the structure and cause of phenotypic variation in fishes from the Northern Hemisphere (most foregoing citations), there have been fewer studies in fishes from South American freshwaters (but see Lundberg and Stager, 1985;Wimberger, 1992;Fink and Machado-Allison, 2001;Langerhans et al, 2003).…”
mentioning
confidence: 99%
“…Previous studies have demonstrated that Wsh morphology could be highly plastic and inXuenced by a wide range of environmental variables such as the prey types and/or feeding modes utilized (e.g., Meyer 1990; Robinson and Wilson 1995;Day and McPhail 1996;Mittelbach et al 1999;Andersson 2003;StauVer and Gray 2004;Olsson and Eklöv 2005), the presence of predators (e.g., Brönmark and Miner 1992;Eklöv and Svanbäck 2006), and the physical environment in which the organism lives (Pakkasmaa and Piironen 2001;Imre et al 2002;McGuigan et al 2003;Peres-Neto and Magnan 2004;Olsson and Eklöv 2005). Despite it being demonstrated in other taxa (e.g., Relyea 2004), our study is, to the best of our knowledge, one of the Wrst to address how individual morphology and behavior responds to a combination of environmental variables in Wsh.…”
Section: Plasticity and Multiple Environmental Variablesmentioning
confidence: 97%